The beach house [videorecording (DVD)] - Liberato, Liana, 1995-; Le Gros, Noah; Nagel, Maryanne; Weber, Jake, 1964- (Shudder, 2020)
Hoping to reignite their relationship, college students Emily and Randall arrive at their weekend getaway only to discover a peculiar older couple already staying there. They all agree to share the home but, after an indulgent night of partying, they're awoken to a living nightmare of apocalyptic proportions. A mysterious airborne microbe has infected the water and it's making its way to the house.